The Imperial Meteor: Time and Velocity in Pedro II’s Journey of 1876–7 - Petter, Augusto (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
This paper analyses the timekeeping practices of Dom Pedro II, Emperor of Brazil, during his journey abroad in 1876–7. The emperor’s preoccupation with scheduling, speed-traveling, and time management is understood here as part of a global context of comparisons between nations within nineteenth-century ideas of progress and universal history. Journalists reported on his journey internationally, focusing on his restlessness, for which they referred to him as an imperial meteor – one who travels the world with unparalleled speed. This study puts Dom Pedro II’s journey outside the national history narrative, placing it in a global perspective. In this way, it is possible to understand how foreign media and the global context of national comparisons of progress in the second half of the nineteenth century took part in the making of the ‘Yankee emperor’, a modern king with progressive values. Dom Pedro, a singular actor who binds the image of monarchy to modern temporality, helps us understand the global phenomenon of the growing preoccupation with mastering time.
p. 55-73
Keywords: Brazilian Empire; Dom Pedro II; modern monarchy; history of time and temporality; Pedro II, Emperor of Brazil, 1825-1891 - travel; time - history - 19th century; time - anthropological aspects; time perception - history